MORPHOLOGICAL CHANGES IN THE HIPPOCAMPUS OF RATS IN ACCELERATED AGING - K. Yu. Maksimova; N. A. Stefanova; S. V. Logvinov (Бюллетень сибирской медицины)
The aim of this work was the analysis of structural changes with age in the hippocampus of senescenceaccelerated OXYS rats when signs of accelerated brain aging are missing (age 14 days), developments (age 5 months), and active progresses (age 15 months). The study was performed on 15 OXYS rats and 15 Wistar rats (as a control). After dislocation, brains were dissected, fixed with 10% formalin, embedded in paraffin, and serially cut in coronal sections (5μm thickness). These sections were stained with Cresyl violet and examined with a photomicroscope (Carl Zeiss Axiostar plus, Germany). The total number of hippocampal pyramidal cells in the CA1, CA3 and the dentate gyrus regions were estimated in 14-dayold, 5and 15-month-old OXYS and Wistar rats (n = 5) on the 5 slices of each brain sections. The number of neurons with chromatolysis, hyperchromatic with darkly stained cytoplasm and shrunken neurons were calculated as degenerative neurons. The pictures obtained with the program Carl Zeiss Axio Vision 8.0 with increasing 10  100, determined the average area bodies and nuclei of neurons (mkm2). The significant structural changes of neurons in the CA1, CA3 and dentate gyrus regions of the hippocampus in OXYS rats at 5 month of age are revealed by light microscopy. This results indicates the early develop neurodegeneration in OXYS rats. The most pronounced morphological changes occur in the CA1 region of the hippocampus of OXYS rats and irreversible. The degenerative changes of neurons in the hippocampus increases by the age of 15 months. Morphometric analysis of the average area of bodies and the nuclei of hippocampal neurons in CA1, CA3 and the dentate gyrus regions of OXYS and Wistar rats at 14 days of age showed no significant interline differences. At 5 months of age in the CA1 region of the hippocampus of OXYS rats was determined a significantly lower average body size and nuclei of pyramidal neurons compared with Wistar rats. With age, these changes have progressed and 15-month-old OXYS rats have a significant decrease in the area bodies and nuclei in all studied regions of the hippocampus compared with Wistar rats. These results confirm the promising use OXYS rats as a model of accelerated brain.